Gene expression of Anx3 in Pb-treated Nicotiana tabacum using a real-time RT-PCR - Phang, Ing Chia; Nawi, Mohd Afiq; Razak, Nurhayati; Ismail, Nor Adibah; Pappusamy, Arokiaraj (2012)
Lead (Pb) is one of the highly persistent, toxic, and widely distributed heavy metal pollutants in the environment. This heavy metal has a tendency to enter human food chain, thus affecting public health. One effective way to remove heavy metals pollutant is by using plants, a technology known as phytoremediation. One such plant that is routinely employed as an experimental model for such studies is Nicotiana tabacum. As tobacco plants are not generally consumed by herbivores, it minimizes the possibility of Pb from entering food chain.